"Fofola e Fala ka e Talanoa e Kainga: A Tongan approach to family violence prevention and intervention". (August 2021) - Havea, Sesimani; Alefaio-Tugia, Siautu; Hodgetts, Darrin
There is limited knowledge of how Pacific-indigenous approaches can aid efforts to curtail violence within the kainga (families). This article documents aspects of the inaugural application of the Tongan conceptual framework of Fofola e fala ka e talanoa e kainga (laying out the mat so families can dialogue) as part of the faith-based Kainga Tu'umalie (prosperous families) family violence intervention and prevention program in Aotearoa New Zealand. Fofola e fala symbolizes a place of safety and refuge for every member of the kainga to freely express their feelings. The first two authors were involved in evaluating the program with the first author engaged in direct observations and being immersed in Kainga Tu'umalie retreats. Given their depth of cultural knowledge and involvement in the development of this program, seven faith-based community leaders were engaged in talanoa (Pacific-indigenous way of dialogue and discussion). Participant accounts form the core basis of our analysis, which highlights the significance of Kainga Tu'umalie as a violence prevention program for Tongan families. Of key consideration is the importance of Tongan-indigenous approaches to reducing family violence that draw from a combination of traditional cultural knowledge and Christian values that are central to the realities of being Tongan today.